The triglyceride glucose-waist circumference index is a predictor of obstructive sleep apnea risk and all-cause and cardiovascular mortality - Yu Zhang; Tao Li; Hai Yu (Scientific Reports)
Abstract Individuals with obstructive sleep apnea (OSA) face greater chances of developing diabetes mellitus. The triglyceride glucose-waist circumference (TyG-WC) index is an effective predictor of insulin resistance; however, its association with OSA and its impact on prognosis in OSA patients remain unclear. Using data from National Health and Nutrition Examination Survey (2005–2008, 2015–2018), we aimed to assess the association between TyG-WC and OSA and investigate its correlation with mortality in individuals with OSA symptoms. Overall, 7,789 participants were included, among whom 3,959 were were identified as having OSA symptoms. Multivariate logistic regression analysis indicated that higher TyG-WC levels were linked to a higher risk of OSA ( odds ratio [OR] = 1.13, 95% confidence interval [CI]: 1.04–1.23, p < 0.05). A non-linear association was found between TyG-WC and mortality, with a significantly increased risk when TyG-WC exceeded 1268.17. Mediation analysis revealed that neutrophils and monocytes accounted for 17.20% and 8.63% of the association with survival time, respectively. These results show that elevated TyG-WC values are independently linked to greater risk of OSA and are non-linearly related to mortality among OSA participants.